Endotracheal Reintubation in Post-Operative Cardiac Surgical Patient other than Surgical Bleeding - Shahana Raza, Kashif Anwar, Neelam Noreen, Mohammed Shafiq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: In recent decades, interventional procedures in cardiac surgery have developed as widely used techniques of treating valvular dysfunctions and coronary artery diseases. Objectives: The main objective of the study is to find the endotracheal reintubation in post-operative cardiac surgical patient other than surgical bleeding. Material and methods: This descriptive study was conducted in Peshawar institute of cardiology during 2018 to 2019. The data was collected with the permission of ethical committee of hospital. The data was collected from those patients who were underwent cardiac bypass surgery in hospital. All demographical data related to age, gender and history of diseases was collected. Results: The data was collected from 122 patients, from these 22 patients were not extubated and none of them survived. The most common indication for surgery was myocardial revascularization (30.6%), followed by valve replacement (22.7%) and thoracic aortic aneurysm repair. Conclusion: It is concluded that reintubation after cardiac surgery is a marker for morbid postoperative period. The reintubation rate in patients undergoing cardiac surgery in our hospital was high.